Cervical cancer screening information flow in Northern regional administrative service in Portugal. (30th September 2020) - Portela, D; Cruz, V; Monteiro, H; Tavares, F
Abstract: Management of a population-based screening program circuit depends on characteristics and technical barriers of its application and implementation. The aim is to clarify the information flow, to understand and build a vision of cervical screening information flows in Northern Regional Health Administration Portuguese Public System and to identify the constraints among them. A total of 5 cluster meetings were presented and two expert interviews were conducted allowing to present an informational flow and its constraints. Aims addressed in each interview where based on the expertise of the interviewed. Cervical cancer screening program depends on the use of SiiMA application. This is an information system for the management of population-based screening program which involves mainly 3 entities and allows a longitudinal data collection and study. Three main constraints were reported. The time for updating data for the list of eligible women was bigger than accorded reaching up to 3 months delay. A duplicate of records and discharges in hospital care since the discharge was done both in the hospital system and the SiiMA platform manually in order to the woman re-enter the screening program. Pendencies were seen due to other screening programs running in parallel which had to be sorted out manually in the regional level or by the entity involved. The existence of a screening application is vital for the implementation purposes of a screening program. The lack of integration of the systems increases bureaucratic work, costs and causes time delay. To improve the efficiency of digital transformation ensuring the quality of the process it is necessary to adapt the design of the health informatic systems to the daily practice and its wants and needs. The strategies of forcing an ever-increasing number of frameworks have demonstrated not to be so effective. Therefore, it is a cornerstone to understand these flows in order to improve its structure, intervention and optimization. Key messages: The existence of a screening digital application is vital but its expanding use arises constraints. Due to the complexity of such programs, a digital strategy is crucial for management and monitoring of the screening at this scale.